Pengaruh Rendam Kaki Air Hangat Terhadap Kualitas Tidur Pada Lansia Penderita Hipertensi Di Kelurahan Lodoyong Kecamatan Ambarawa Kabupaten Semarang - Meisya Dicki Candra; Eko Susilo; Wulansari Wulansari (Universitas Ngudi Waluyo, 2019)
Sleep disorders attack 50% elderly. Elderly people are at risk of having sleep disorder caused by many factors, one of which is hypertension. Poor sleep quality can cause physiological and psychological balance disorders. Warm water foot soak as one alternative action for increase sleeping quality in elderly with hypertension because of the relaxation effect. This study aim to determine the effect of warm water foot soak toward sleeping quality in elderly with hypertension at Lodoyong Village Ambarawa Subdistrict Semarang Regency. Methods is Pre experimental with one group pre test-post test design. The samples of 26 people were taken by purposive sampling method. Data analysis bivariate (Wilcoxon Statistics Test). 26 elderly have good sleeping quality (100%). Bivariate analysis shows there is effect of warm water foot soak toward sleeping quality in elderly with hypertension at Lodoyong Village Ambarawa Subdistrict Semarang Regency with p Value 0,001. As one alternative action for increase sleeping quality in elderly with hypertension. The elderly with hypertension should do warm water foot soak so that it can be done continuously on night. So there isn’t decrease in sleeping quality.Key words: warm water foot soak, sleeping quality, hypertension, elderly